Sustainability of Earthen Construction in North Cyprus - Pekrioğlu Balkıs , Ayşe; Balkıs, Mete Mutlu (ICONARCH International Congress of Architecture and Planning, 2012)
Sustainability depends on the maintenance of the natural world and natural resources. Built environment has the greatest impact on environment. Reducing energy consumption of construction and life cycle of the buildings will contribute to the sustainability. In this study, traditional structures of North Cyprus and their effective structures for environment protection have been analyzed. Traditional structures in Cyprus were built with natural materials such as stone and earth that creates healthy indoors, concerning the climatic conditions. Structures constructed with industrial materials no longer provide indoor comfort. Lots of energy is being used to provide indoor climate in today’s buildings. A very large part of consumed energy in Cyprus is being used by residential sector. Earth is a natural building material made from sand, clay, and water. They may also be produced with some kind of fibrous or organic material (sticks, straw, dung) which is shaped into bricks using frames and dried in the sun. Earthen structures are extremely durable and account for some of the oldest extant buildings on the planet. Earth’s strength and durability can be improved if needed. Dense forms of stabilized earthen construction have high thermal mass and able to store heat and provide long term energy savings for cooling in summer and heating in winter so, provide bioclimatic comfort for health with a suitable humidity and thereby balance indoor climate. Due to their high thermal comfort and being cultural characteristic properties of Cyprus, sustainability of Earthen structures are important. Earthen construction is not meeting with today’s requirements because it has some disability such as low water resistance and low earthquake resistance. But these properties can be stabilized with gypsum. Revival of earthen construction will protect earthen architectural heritage.